Highly efficient deep-penetrating nanoemulsion and preparation method thereof
Patent Information
- Application Number
- CN202611186925.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-08-06
AI Technical Summary
Existing nanoemulsions suffer from insufficient penetration driving force, low penetration efficiency, and limited depth in terms of deep penetration. They also lack a mechanism to actively drive droplets to migrate into the deeper layers of the skin, making it impossible to achieve layer-by-layer delivery from the surface to the interior.
A dual-mode synergistic driving system was constructed by combining isosorbide dimethyl ether and monoterpene carbonate. Isosorbide dimethyl ether served as a short-acting initiator, while monoterpene carbonate served as a long-acting diffusive driving agent. Through the synergistic effect of interfacial tension gradient and interfacial film, the self-driven directional migration of nanoemulsion droplets was achieved.
It achieves active penetration of nanoemulsion droplets, quickly initiates and maintains its penetration ability, and the active ingredients are enriched in the deep dermis, possessing efficient, continuous and deep active penetration capabilities.
Smart Images

Figure CN122664862B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanoemulsion technology, specifically relating to a highly efficient deep-penetrating nanoemulsion and its preparation method. Background Technology
[0002] Nanoemulsions are widely used for transdermal delivery of active ingredients in cosmetics due to their advantages such as small particle size, large specific surface area, and good skin affinity. Studies have shown that nanoemulsions can significantly improve the skin penetration performance of active ingredients; even without the addition of penetration enhancers, nanoemulsions can increase the skin penetration rate of active ingredients by nearly three times. Therefore, nanoemulsions are considered an important carrier form for overcoming the stratum corneum barrier and achieving efficient delivery of active ingredients.
[0003] However, existing nanoemulsions still have significant limitations in deep penetration. First, the penetration driving force is insufficient. The transdermal absorption of existing nanoemulsions mainly relies on passive diffusion. Active ingredients slowly cross the skin barrier based on their own concentration gradient, lacking directional driving force. A large number of active ingredients are intercepted by the stratum corneum before reaching the target site, resulting in low penetration efficiency and limited depth. Second, the penetration enhancement methods are limited. To improve transdermal efficiency, existing technologies usually add chemical penetration enhancers to increase permeability by disturbing the orderly arrangement of lipids in the stratum corneum. However, active ingredients still need to rely on passive diffusion to cross the opened channels, and the deep delivery efficiency is still not ideal. Third, the carrier function is limited. Existing nanoemulsions only serve as passive carriers of active ingredients and lack a mechanism to actively drive droplet migration into the deeper layers of the skin, failing to achieve layer-by-layer delivery from the surface to the interior.
[0004] Therefore, how to provide a continuous and controllable driving force for deep penetration of nanoemulsions, based on the use of chemical penetration enhancers to open the penetration channels, so that active ingredients can actively penetrate the stratum corneum and accumulate in the dermis, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a highly efficient deep-penetrating nanoemulsion and its preparation method to solve the above-mentioned technical problems.
[0006] To achieve the above-mentioned technical objectives, the technical solution of the present invention is as follows:
[0007] S1. Dissolve the additive in deionized water, heat to 40~50℃, and stir until completely dissolved to obtain the aqueous phase;
[0008] S2. Mix monoterpene carbonate, oil phase matrix, composite emulsifier and active ingredient, heat to 40~50℃, stir until completely dissolved, to obtain oily premix;
[0009] S3. Under stirring conditions of 40~50℃ and 300~500rpm, the oily premix is slowly injected into the aqueous phase at an injection rate of 1~5mL / min. The non-equilibrium distribution of the composite emulsifier at the oil-water interface generates an interfacial tension gradient, which drives the oil phase to spontaneously break down into nano-sized droplets, thus obtaining a spontaneously emulsified emulsion.
[0010] S4. Cool the spontaneously emulsified emulsion to room temperature, add isosorbide dimethyl ether under sealed conditions, stir at 200-300 rpm for 5-10 min, and homogenize at room temperature and 300-500 bar pressure for 1-2 cycles to obtain a highly efficient deep-penetrating nanoemulsion.
[0011] As a further improvement, the preparation method of the monoterpene carbonate is as follows: terpene alcohol is mixed with diethyl carbonate, an alkaline catalyst is added, and the mixture is stirred at 80~100℃ for 4~8h. During the reaction, the byproduct ethanol is continuously removed by distillation. After the reaction is completed, the mixture is cooled to room temperature and purified by vacuum distillation and column chromatography to obtain the monoterpene carbonate.
[0012] As a further improvement, the terpene alcohol is menthol or thymol; the alkaline catalyst is sodium ethoxide or potassium carbonate; the molar ratio of the terpene alcohol to diethyl carbonate is 1:1~3; and the amount of the alkaline catalyst is 0.5~3% of the total mass of the terpene alcohol and diethyl carbonate.
[0013] As a further improvement, the mass ratio of isosorbide dimethyl ether to monoterpene carbonate is 1:1~2.
[0014] As a further improvement, in step S1, the auxiliary agent is prepared by compounding glycerol and sodium hyaluronate, with a mass ratio of glycerol to sodium hyaluronate of 3~4:1.
[0015] As a further improvement, in step S2, the oil phase matrix is caprylic triglyceride or caprylic triglyceride.
[0016] As a further improvement, in step S2, the composite emulsifier is composed of polysorbate 80 and sucrose stearate, with a mass ratio of polysorbate 80 to sucrose stearate of 3~5:1.
[0017] As a further improvement, in step S2, the active ingredient is any one of vitamin C derivatives, polypeptides, and retinol.
[0018] As a further improvement, the content of each component by mass percentage is as follows: 1-3% of the adjuvants, 2-6% of the total of isosorbide dimethyl ether and monoterpene carbonate, 6-12% of the oil phase matrix, 2-5% of the compound emulsifier, 2-4% of the active ingredients, and the balance being deionized water.
[0019] The present invention also provides a highly efficient deep-penetrating nanoemulsion.
[0020] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0021] This invention provides a highly efficient deep-penetrating nanoemulsion and its preparation method. By combining isosorbide dimethyl ether and monoterpene carbonate to form a dual-mode synergistic penetration-enhancing system, isosorbide dimethyl ether acts as a short-acting initiator and monoterpene carbonate acts as a long-acting diffusion-enhancing agent, realizing the self-driven directional migration of nanoemulsion droplets and breaking through the transdermal limitation of traditional nanoemulsions that rely on passive diffusion.
[0022] In the initial application stage, isosorbide dimethyl ether, possessing both interfacial activity and stratum corneum affinity, rapidly diffuses from the emulsion interface film into the lipid gaps of the stratum corneum, instantly establishing a stable interfacial tension gradient between the droplets and the skin. The emulsion fluid is continuously drawn by the high-tension skin interface, driving the nanodroplets to actively approach the skin surface, achieving rapid initiation of penetration. In the middle stage of penetration, monoterpene carbonates are continuously released from the interface film, maintaining a steady-state concentration gradient for sustained penetration. Furthermore, after release, the terpene groups of monoterpene carbonates actively disturb the orderly arrangement of stratum corneum lipids, opening penetration channels. The carbonate skeleton, possessing both interfacial activity and stratum corneum affinity, achieves molecular anchoring. This triple mechanism works synergistically over time and progressively in space, enabling the active ingredients to actively penetrate the stratum corneum and epidermal barriers, accumulating in the deep dermis, thus endowing the nanoemulsion with efficient, continuous, and deep active penetration capabilities.
[0023] This invention has significant advantages in formulation design and preparation process: the compound emulsifier, which combines polysorbate 80 and sucrose stearate, utilizes the difference in diffusion rates between the two at the oil-water interface to generate a non-equilibrium distribution, driving the chemical Marangoni effect to achieve spontaneous emulsification. Combined with low-pressure homogenization and fine-tuning, a nanoemulsion with uniform particle size can be obtained. The preparation process is mild and energy-efficient, avoiding the shear loss of high-pressure homogenization. In addition, the monoterpene carbonate, as a long-acting component, combines the interfacial activity of carbonate groups, the lipid perturbation ability of terpene groups in the stratum corneum, and the interfacial film stabilization effect of long-chain hydrophobic structure. Its synergy with isosorbide dimethyl ether is not only reflected in the enhanced transdermal penetration, but also in the joint maintenance of the integrity and density of the oil-water interfacial film during storage. The raw materials of this nanoemulsion are readily available, the preparation process is simple, and the stability is good, making it suitable for deep transdermal delivery of various types of active ingredients. Attached Figure Description
[0024] Figure 1 This is an ATR-FTIR image of the menthol carbonate prepared in Example 1. Detailed Implementation
[0025] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or manufacturer's conditions shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0026] Example 1: A method for preparing a highly efficient deep-penetrating nanoemulsion, comprising the following steps:
[0027] 1. Menthol and diethyl carbonate were mixed at a molar ratio of 1:2 and added to a reactor. The reaction system was dehydrated beforehand. Sodium ethoxide (1.75% of the total mass of menthol and diethyl carbonate) was added as a catalyst. Under nitrogen protection, the mixture was heated to 100°C and stirred under reflux for 6 hours. During the reaction, the byproduct ethanol was continuously removed by distillation to shift the reaction equilibrium towards the product. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to remove unreacted diethyl carbonate. The crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 8:1) to obtain menthol carbonate.
[0028] The reaction expression for this step is as follows:
[0029] ;
[0030] The ATR-FTIR image of the menthol carbonate prepared in this embodiment is as follows: Figure 1 As shown; from Figure 1 It can be seen from this that at 2950cm -1 The strong absorption peak is attributed to the saturated CH stretching vibration, consistent with the characteristics of numerous saturated CH bonds in the menthol skeleton and carbonate groups; at 1745 cm⁻¹... -1 The strong absorption peak at 1270 cm⁻¹ is attributed to the C=O stretching vibration of the carbonate carbonyl group, which is key evidence of the successful esterification reaction; -1 The absorption peak appearing at 3600-3200 cm⁻¹ is attributed to the CO stretching vibration; the absorption peak at 3600-3200 cm⁻¹ is also attributed to the CO stretching vibration. -1 The absence of a prominent OH stretching vibration peak within the region indicates that the hydroxyl groups of the menthol raw material have completely reacted, confirming the completeness of the esterification reaction. These characteristic absorption peaks collectively demonstrate that menthol and diethyl carbonate successfully formed the target product, menthol carbonate, via transesterification.
[0031] 2. Dissolve 1.5 g glycerol and 0.5 g sodium hyaluronate in 78.5 g deionized water, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 2.8 g polysorbate 80 and 0.7 g sucrose stearate to obtain a composite emulsifier; add 2.4 g menthol carbonate, 9.0 g decanoic acid triglyceride, the above composite emulsifier, and 3 g vitamin C ethyl ether sequentially to a beaker, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0032] 3. Under constant temperature water bath conditions of 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase. Due to the different diffusion rates of the two components, an instantaneous non-equilibrium concentration gradient was formed at the oil-water interface, resulting in a chemical Marangoni effect, which drove the oil-water interface to spontaneously bend and break down, forming nanoscale emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow the spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0033] 4. Cool the self-emulsified emulsion to room temperature, add 1.6g of isosorbide dimethyl ether under sealed conditions, and stir at 250rpm for 8min to ensure that the isosorbide dimethyl ether is fully distributed to the oil-water interface. Transfer to a high-pressure homogenizer and homogenize for one cycle at room temperature and 400 bar pressure to further homogenize the particle size. After homogenization, filter through a 0.22 μm filter membrane and fill into a sealed container to obtain a highly efficient deep-penetrating nanoemulsion.
[0034] Example 2: A method for preparing a highly efficient deep-penetrating nanoemulsion, comprising the following steps:
[0035] 1. Thymol and diethyl carbonate were mixed at a molar ratio of 1:3 and added to a reactor. The reaction system was dehydrated beforehand. Potassium carbonate (3% of the total mass of thymol and diethyl carbonate) was added as a catalyst. Under nitrogen protection, the mixture was heated to 100°C and stirred under reflux for 4 hours. During the reaction, the byproduct ethanol was continuously removed by distillation to shift the reaction equilibrium towards the product. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to remove unreacted diethyl carbonate. The crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 10:1) to obtain thymol carbonate.
[0036] 2. Dissolve 2.4 g glycerol and 0.6 g sodium hyaluronate in 70 g deionized water, heat to 50 °C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 4.17 g polysorbate 80 and 0.83 g sucrose stearate to obtain a composite emulsifier; add 4 g thymol carbonate, 12 g caprylic acid triglyceride, the above composite emulsifier and 4 g palmitoyl pentapeptide-4 sequentially to a beaker, heat to 50 °C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0037] 3. Under constant temperature water bath conditions of 50℃ and magnetic stirring at 500 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 5 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase. Due to the different diffusion rates of the two components, an instantaneous non-equilibrium concentration gradient was formed at the oil-water interface, resulting in a chemical Marangoni effect, which drove the oil-water interface to spontaneously bend and break down, forming nanoscale emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow the spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0038] 4. Cool the self-emulsified emulsion to room temperature, add 2g of isosorbide dimethyl ether under sealed conditions, and stir at 300rpm for 5min to ensure that the isosorbide dimethyl ether is fully distributed to the oil-water interface. Transfer to a high-pressure homogenizer and homogenize for 2 cycles at room temperature and 300 bar pressure to further homogenize the particle size. After homogenization, filter through a 0.22 μm filter membrane and fill into a sealed container to obtain a highly efficient deep-penetrating nanoemulsion.
[0039] Example 3: A method for preparing a highly efficient deep-penetrating nanoemulsion, comprising the following steps:
[0040] 1. Menthol and diethyl carbonate were mixed at a molar ratio of 1:1 and added to a reactor. The reaction system was dehydrated beforehand. Potassium carbonate (0.5% of the total mass of menthol and diethyl carbonate) was added as a catalyst. Under nitrogen protection, the mixture was heated to 80°C and stirred under reflux for 8 hours. During the reaction, the byproduct ethanol was continuously removed by distillation to shift the reaction equilibrium towards the product. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to remove unreacted diethyl carbonate. The crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 10:1) to obtain menthol carbonate.
[0041] 2. Dissolve 0.75g glycerol and 0.25g sodium hyaluronate in 87g deionized water, heat to 40℃, and stir magnetically at 300rpm for 15min until completely dissolved to obtain an aqueous phase; mix 1.5g polysorbate 80 and 0.5g sucrose stearate to obtain a composite emulsifier; add 1g menthol carbonate, 6g caprylic triglyceride, the above composite emulsifier and 2g retinol sequentially to a beaker, heat to 40℃, and stir magnetically at 300rpm for 15min until completely dissolved to obtain a clear and transparent oily premix;
[0042] 3. Under constant temperature water bath conditions of 40℃ and magnetic stirring at 300 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 1 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase. Due to the different diffusion rates of the two components, an instantaneous non-equilibrium concentration gradient was formed at the oil-water interface, resulting in a chemical Marangoni effect, which drove the oil-water interface to spontaneously bend and break, forming nanoscale emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow the spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0043] 4. Cool the self-emulsified emulsion to room temperature, add 1g of isosorbide dimethyl ether under sealed conditions, and stir at 200rpm for 10min to ensure that the isosorbide dimethyl ether is fully distributed to the oil-water interface. Transfer to a high-pressure homogenizer and homogenize for one cycle at room temperature and 500 bar pressure to further homogenize the particle size. After homogenization, filter through a 0.22 μm filter membrane and fill into a sealed container to obtain a highly efficient deep-penetrating nanoemulsion.
[0044] Comparative Example 1: A method for preparing a nanoemulsion, differing from Example 1 in that it does not contain the dual-mode driving agents, namely menthol carbonate and isosorbide dimethyl ether, and includes the following steps:
[0045] 1. Dissolve 1.5 g glycerol and 0.5 g sodium hyaluronate in 82.5 g deionized water, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 2.8 g polysorbate 80 and 0.7 g sucrose stearate to obtain a composite emulsifier; add 9.0 g decanoic acid triglyceride, the above composite emulsifier, and 3 g vitamin C ethyl ether sequentially to a beaker, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0046] 2. Under constant temperature water bath conditions of 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase, forming emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0047] 3. Transfer the spontaneously emulsified emulsion to a high-pressure homogenizer and homogenize it for one cycle at room temperature and 400 bar pressure to further homogenize the particle size. After homogenization, filter it through a 0.22 μm filter membrane and fill it into a sealed container to obtain the nanoemulsion.
[0048] Comparative Example 2: A method for preparing a nanoemulsion, differing from Example 1 in that it contains only a short-acting initiator, isosorbide dimethyl ether, and includes the following steps:
[0049] 1. Dissolve 1.5 g glycerol and 0.5 g sodium hyaluronate in 78.5 g deionized water, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 2.8 g polysorbate 80 and 0.7 g sucrose stearate to obtain a composite emulsifier; add 9.0 g decanoic acid triglyceride, the above composite emulsifier, and 3 g vitamin C ethyl ether sequentially to a beaker, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0050] 2. Under constant temperature water bath conditions of 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase, forming emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0051] 3. Cool the self-emulsified emulsion to room temperature, add 4g of isosorbide dimethyl ether under sealed conditions, and stir at 250rpm for 8min to ensure that the isosorbide dimethyl ether is fully distributed to the oil-water interface. Transfer to a high-pressure homogenizer and homogenize for one cycle at room temperature and 400 bar pressure to further homogenize the particle size. After homogenization, filter through a 0.22 μm filter membrane and fill into a sealed container to obtain a highly efficient deep-penetrating nanoemulsion.
[0052] Comparative Example 3: A method for preparing a nanoemulsion, differing from Example 1 in that it contains only a long-lasting diffusion-driving agent, namely menthol carbonate, and includes the following steps:
[0053] 1. Menthol and diethyl carbonate were mixed at a molar ratio of 1:2 and added to a reactor. The reaction system was dehydrated beforehand. Sodium ethoxide (1.75% of the total mass of menthol and diethyl carbonate) was added as a catalyst. Under nitrogen protection, the mixture was heated to 100°C and stirred under reflux for 6 hours. During the reaction, the byproduct ethanol was continuously removed by distillation to shift the reaction equilibrium towards the product. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to remove unreacted diethyl carbonate. The crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 8:1) to obtain menthol carbonate.
[0054] 2. Dissolve 1.5 g glycerol and 0.5 g sodium hyaluronate in 78.5 g deionized water, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 2.8 g polysorbate 80 and 0.7 g sucrose stearate to obtain a composite emulsifier; add 4 g menthol carbonate, 9.0 g decanoic acid triglyceride, the above composite emulsifier and 3 g vitamin C ethyl ether sequentially to a beaker, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0055] 3. Under constant temperature water bath conditions of 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase, forming emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0056] 4. Transfer the spontaneously emulsified emulsion to a high-pressure homogenizer and homogenize it for one cycle at room temperature and 400 bar pressure to further homogenize the particle size. After homogenization, filter it through a 0.22 μm filter membrane and fill it into a sealed container to obtain the nanoemulsion.
[0057] Comparative Example 4: A method for preparing a nanoemulsion, differing from Example 1 in that diethyl carbonate is used instead of monoterpene carbonate, comprising the following steps:
[0058] 1. Dissolve 1.5 g glycerol and 0.5 g sodium hyaluronate in 78.5 g deionized water, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain an aqueous phase; mix 2.8 g polysorbate 80 and 0.7 g sucrose stearate to obtain a composite emulsifier; add 2.4 g diethyl carbonate, 9.0 g triglyceride decanoate, the above composite emulsifier, and 3 g vitamin C ethyl ether sequentially to a beaker, heat to 45°C, and stir magnetically at 300 rpm for 15 min until completely dissolved to obtain a clear and transparent oily premix;
[0059] 2. Under constant temperature water bath conditions of 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min. During the injection process, the composite emulsifier (polysorbate 80 and sucrose stearate) diffused from the oil phase to the aqueous phase, forming emulsion droplets. After the injection was completed, stirring was continued for 5 min to allow spontaneous emulsification to proceed fully, resulting in a spontaneously emulsified emulsion.
[0060] 3. Cool the self-emulsified emulsion to room temperature, add 1.6g of isosorbide dimethyl ether under sealed conditions, and stir at 250rpm for 8min to ensure that the isosorbide dimethyl ether is fully distributed to the oil-water interface. Transfer to a high-pressure homogenizer and homogenize for one cycle at room temperature and 400 bar pressure to further homogenize the particle size. After homogenization, filter through a 0.22 μm filter membrane and fill into a sealed container to obtain a highly efficient deep-penetrating nanoemulsion.
[0061] Comparative Example 5: A method for preparing a nanoemulsion, differing from Example 1 in that isosorbide dimethyl ether is added to the oil phase in advance for simultaneous emulsification, including the following steps:
[0062] 1. Menthol and diethyl carbonate were mixed at a molar ratio of 1:2 and added to a reactor. The reaction system was dehydrated beforehand. Sodium ethoxide (1.75% of the total mass of menthol and diethyl carbonate) was added as a catalyst. Under nitrogen protection, the mixture was heated to 100°C and stirred under reflux for 6 hours. During the reaction, the byproduct ethanol was continuously removed by distillation to shift the reaction equilibrium towards the product. After the reaction was completed, the mixture was cooled to room temperature and distilled under reduced pressure to remove unreacted diethyl carbonate. The crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 8:1) to obtain menthol carbonate.
[0063] 2. Dissolve 1.5g glycerol and 0.5g sodium hyaluronate in 78.5g deionized water, heat to 45℃, and stir magnetically at 300rpm for 15min until completely dissolved to obtain an aqueous phase; mix 2.8g polysorbate 80 and 0.7g sucrose stearate to obtain a composite emulsifier; add 1.6g isosorbide dimethyl ether, 2.4g menthol carbonate, 9.0g decanoic acid triglyceride, the above composite emulsifier, and 3g vitamin C ethyl ether sequentially to a beaker, heat to 45℃, and stir magnetically at 300rpm for 15min until completely dissolved to obtain an oily premix;
[0064] 3. Under the conditions of constant temperature water bath at 45℃ and magnetic stirring at 400 rpm, the oily premix was slowly injected into the aqueous phase at an injection rate of 3 mL / min to obtain a self-emulsifying emulsion.
[0065] 4. Transfer the spontaneously emulsified emulsion to a high-pressure homogenizer and homogenize it for one cycle at room temperature and 400 bar pressure. After homogenization, filter it through a 0.22 μm filter membrane and fill it into a sealed container to obtain the nanoemulsion.
[0066] Performance testing
[0067] 1. Particle size and potential determination
[0068] The nanoemulsions prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to particle size and zeta potential measurements. 10 μL of each sample was taken into a centrifuge tube, diluted with deionized water, and the particle size and zeta potential were measured at a scattering angle of 90° and a temperature of 25°C. Each sample was measured in triplicate, and the average of the three measurements was taken as the final value.
[0069] The test results are shown in Table 1:
[0070] Table 1. Results of particle size and potential measurements
[0071]
[0072] In step S3 of this invention, after the oily premix is injected into the aqueous phase, the composite emulsifier (polysorbate 80 and sucrose stearate) forms a non-equilibrium distribution at the oil-water interface, that is, the two emulsifier components diffuse from the oil phase to the aqueous phase at different rates, generating an instantaneous interfacial tension gradient at the oil-water interface, driving the chemical Marangoni effect, causing the oil-water interface to spontaneously bend and break, forming nanoscale emulsion droplets; the presence of isosorbide dimethyl ether and monoterpene carbonate reduces the oil-water interfacial tension, making the interface more prone to disturbance and breakage under non-equilibrium conditions.
[0073] As can be seen from Table 1, the particle size range of the samples prepared in Examples 1-3 is between 135 and 142 nm, and the PDI is less than 0.16. This indicates that the nanoemulsion prepared by the present invention has a small particle size and uniform distribution. This confirms that the non-equilibrium distribution of the composite emulsifier at the oil-water interface during spontaneous emulsification can effectively generate an interfacial tension gradient, drive the chemical Marangoni effect, and cause the oil-water interface to spontaneously bend and break to form nanoscale droplets. Furthermore, the low-pressure homogenization fine-tuning process further homogenizes the particle size.
[0074] Comparative Example 1, without the addition of the dual-mode driving agent, had the largest particle size and the highest PDI, indicating that the oil-water interfacial tension was high without the driving agent, the interfacial instability caused by non-equilibrium partitioning was reduced, and the spontaneous emulsification efficiency was decreased. This confirms the key role of isosorbide dimethyl ether and monoterpene carbonate in reducing oil-water interfacial tension and promoting interfacial disturbance and rupture.
[0075] Comparative Example 2 contained only isosorbide dimethyl ether as a short-acting initiator. Its particle size and PDI were higher than those of Example 1. This indicates that although the short-acting initiator can quickly reduce interfacial tension and initiate spontaneous emulsification in the early stage, the gradient formed by the instantaneous keratin partitioning is short-lived. In the later stage, there is a lack of long-acting components to maintain the interfacial tension gradient, and the duration of the non-equilibrium partitioning effect is insufficient. This results in limited persistence and sufficiency of interfacial disturbance during spontaneous emulsification, and incomplete droplet formation.
[0076] Comparative Example 3 contains only menthol carbonate as a long-lasting diffusion driver. Its particle size and PDI are also higher than those of Example 1. This indicates that although the long-lasting component can continuously reduce interfacial tension, the lack of a short-lasting initiator component to quickly establish the initial interfacial tension gradient results in a lower spontaneous emulsification trigger efficiency and insufficient interfacial disturbance, which also affects the refinement and homogenization of droplets.
[0077] Comparative Example 4 used a combination of isosorbide dimethyl ether and diethyl carbonate as a driving agent. Its particle size and PDI were superior to those of Comparative Examples 1-3. The only difference between Comparative Example 4 and Example 1 was the long-lasting diffusing component. Comparative Example 4 used the known transdermal penetration enhancer diethyl carbonate, while Example 1 used monoterpene carbonate. The difference between the two in terms of particle size and PDI was not significant, indicating that in terms of spontaneous emulsification efficiency, both diethyl carbonate and menthol carbonate can effectively reduce interfacial tension and maintain the non-equilibrium partitioning effect.
[0078] In Comparative Example 5, isosorbide dimethyl ether was added to the oil phase in advance, and the particle size and PDI were higher than those in Example 1. This indicates that the early addition of isosorbide dimethyl ether to the oil phase to participate in the emulsification process resulted in some of it volatilizing or being pre-distributed to the aqueous phase, which weakened its ability to quickly establish an interfacial tension gradient during the subsequent spontaneous emulsification process.
[0079] The above results indicate that the synergistic effect of the short-acting component (isosorbide dimethyl ether) and the long-acting component (monoterpene carbonate) in the dual-mode driving agent is the key to achieving efficient spontaneous emulsification. The short-acting component is responsible for rapidly establishing the interfacial tension gradient and triggering interfacial disturbances, while the long-acting component is responsible for continuously maintaining the non-equilibrium distribution state and ensuring sufficient droplet refinement. Both are indispensable.
[0080] 2. Storage stability test
[0081] The nanoemulsions prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to storage stability tests. Samples were placed in beakers and stored at 4℃ and 40℃ for 30 days, respectively. Particle size and Zeta potential were then measured. 10 μL of each sample was taken into centrifuge tubes, diluted with deionized water, and tested at a scattering angle of 90° and a temperature of 25℃. Each sample was tested in triplicate, and the average of the three tests was taken as the final value. The test results are shown in Table 2.
[0082] Table 2 Storage stability test results
[0083]
[0084] As shown in Table 2, after 30 days of storage at 4℃ and 40℃, the particle size and Zeta potential of Examples 1-3 did not change significantly, indicating that the nanoemulsions prepared by this invention have good thermodynamic and kinetic stability. This is attributed to the synergistic effect of isosorbide dimethyl ether and monoterpene carbonate dual-mode driving agents in this invention. Isosorbide dimethyl ether is added at room temperature and fully distributed into the interfacial film, where it is protected. During storage, it is locked in by the oil-water interfacial film, resulting in extremely low escape from the air. Monoterpene carbonate, through the anchoring of carbonate groups on the interfacial film and the hydrophobic interaction between terpene groups and oil phase molecules, continuously maintains the integrity and compactness of the interfacial film. Together, they ensure the stability of the emulsion.
[0085] Comparative Example 1, without the addition of a driving agent, had the largest initial particle size. After 30 days of storage at 40°C, the particle size increased by 30 nm, indicating that the nanoemulsion without the driving agent exhibited significant droplet aggregation during storage. This is because the lack of driving agent molecules filling the interfacial film resulted in insufficient interfacial film strength, which could not effectively suppress the collision and coalescence between droplets.
[0086] Comparative Example 2 showed a significantly higher increase than Example 1 at 4°C and 40°C. This is because isosorbide dimethyl ether slowly migrates out of the oil-water interface film, causing a decrease in the content of the driving component within the interface, collapse of the oil phase interface layer structure, damage to the integrity of the interface film, and irreversible aggregation of some droplets.
[0087] In Comparative Example 3, the particle size increased from the initial 145 nm to 151 nm and 168 nm at 4 °C and 40 °C, respectively. Although monoterpene carbonates have low volatility, single interface modification is insufficient to maintain the long-term structural integrity of the interface film in the absence of short-acting components. The droplets still grew to a certain extent during storage.
[0088] In Comparative Example 4, the particle size increased from the initial 140 nm to 145 nm and 158 nm at 4℃ and 40℃, respectively. Diethyl carbonate has low volatility, but its molecular weight is small. As a small molecule carbonate, its anchoring ability in the interfacial membrane is relatively limited. During long-term storage, some diethyl carbonate molecules may gradually migrate from the interfacial membrane to the aqueous phase or slowly migrate out of the system, resulting in a reduction of the effective components in the interfacial membrane. Diethyl carbonate lacks the stratum corneum lipid affinity of terpene groups and cannot enhance the stable binding with the interfacial membrane through the hydrophobic interaction of terpene groups like monoterpene carbonates. Therefore, the stability of its interfacial membrane structure during long-term storage is lower than that of monoterpene carbonates.
[0089] After being stored at 4°C and 40°C for 30 days, Comparative Example 5 showed a significantly larger increase in particle size and a significantly larger decrease in zeta potential than Example 1. This indicates that the addition of isosorbide dimethyl ether at room temperature after spontaneous emulsification ensures that isosorbide dimethyl ether is effectively encapsulated and locked in by the oil-water interface film, and is protected by the interface film during storage, making it less likely to escape or migrate.
[0090] In summary, Examples 1-3 of the present invention exhibited excellent storage stability at 4°C and 40°C. This is attributed to the synergistic effect of the dual-mode driving agents of isosorbide dimethyl ether and monoterpene carbonate. Although a small amount of isosorbide dimethyl ether migrates out of the interfacial membrane, causing trace component loss, the monoterpene carbonate maintains the integrity and compactness of the interfacial membrane through the anchoring of its carbonate groups on the interfacial membrane and the hydrophobic interaction between the terpene groups and the oil phase molecules.
[0091] 3. Deep transdermal penetration test
[0092] The highly efficient deep-penetrating nanoemulsion samples prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to in vitro deep transdermal penetration tests.
[0093] Take fresh, isolated pig back skin, carefully remove the subcutaneous fat tissue with a scalpel, and remove any remaining hair on the surface with tweezers; rinse the treated pig skin with pH 7.4 phosphate buffer, wrap it in aluminum foil, and freeze it at -20°C for later use; before the experiment, thaw the pig skin naturally in pH 7.4 PBS, wipe off the buffer solution on the skin, check the skin integrity to ensure there is no damage, and cut it into pieces of approximately 2.5 cm × 2.5 cm for later use.
[0094] The prepared pigskin was fixed between the receiving and supply cells of the Franz diffusion cell, with the stratum corneum facing upwards towards the supply cell and the dermis facing towards the receiving cell, ensuring a good seal between the skin and the edge of the diffusion cell without the formation of air bubbles. PBS (pH=7.4) containing 5% Tween 80 was injected into the receiving cell as the receiving solution; 2 mL of Example 1 and Comparative Example 1-4 nanoemulsion samples diluted 5 times were added to the supply cell; the assembled Franz diffusion cell was placed in a transdermal diffusion apparatus, and the experimental conditions were set as follows: temperature 37℃, stirring speed 400 r / min, and transdermal time 12 h.
[0095] After transdermal treatment, the pigskin was removed from the diffusion cell, and any remaining sample on the skin surface was wiped clean with absorbent cotton. The content of the active ingredient was then measured.
[0096] (1) Stratum corneum sample: 21 layers of skin on the surface of pig skin were removed with 3M tape. The first layer was discarded and the remaining 20 layers of tape were placed in a 15mL centrifuge tube. 2mL of isopropanol was added, and the mixture was sonicated for 30min. After centrifugation at 5000r / min for 30min, the supernatant was filtered through a 0.22μm organic filter membrane. The content of active ingredients was determined by HPLC, which is the amount of active ingredients retained in the stratum corneum.
[0097] (2) Epidermal sample: The remaining skin after removing the stratum corneum was heated at 40℃ for 15s, and the lower epidermal layer was carefully cut off with a scalpel. After being cut into pieces, it was placed in a 15mL centrifuge tube, 2mL of isopropanol was added, and the mixture was sonicated for 30min. After centrifugation at 5000 r / min for 30min, the supernatant was filtered through a 0.22μm organic filter membrane, and the content of active ingredients was determined by HPLC, which is the amount of active ingredients retained in the epidermal layer.
[0098] (3) Dermal sample: The remaining skin tissue was cut into small pieces and placed in a 15 mL centrifuge tube. 2 mL of isopropanol was added, and the mixture was sonicated for 30 min. After centrifugation at 5000 r / min for 30 min, the supernatant was collected, filtered, and the content of active ingredients was determined by HPLC. This is the amount of active ingredients retained in the dermis. Each experiment was repeated three times, and the average value was taken as the final result.
[0099] The experimental results are shown in Table 3.
[0100] Table 3 Distribution of active ingredients in different layers of the skin
[0101]
[0102] As shown in Table 3, the retention rate of the active ingredient in the dermis of Example 1 is significantly higher than that of Comparative Examples 1-5, and the dermal penetration rate is significantly better than that of the comparative examples. This indicates that the nanoemulsion of the present invention, driven by the chemical Marangoni effect, can effectively carry the active ingredient across the stratum corneum and epidermal barrier to reach the dermis, achieving true deep penetration. Furthermore, the dermal penetration rates of Examples 2 and 3 are similar to those of Example 1, demonstrating that the technical solution of the present invention has good applicability and stable deep penetration effect for both peptides and retinol.
[0103] Comparative Example 1, which does not contain a dual-mode driving agent, had its active ingredients mainly retained in the stratum corneum, with the lowest penetration rate in the dermis. This indicates that without a driving agent, the nanoemulsion cannot achieve deep delivery by relying solely on passive diffusion.
[0104] Comparative Example 2 contains only isosorbide dimethyl ether. Its active ingredient is more distributed in the stratum corneum and active epidermal layer, but its penetration rate in the dermal layer is still significantly lower than that in Example 1. This indicates that although isosorbide dimethyl ether can establish an initial surface tension gradient by rapidly distributing to the stratum corneum, due to the lack of sustained action of long-acting components, the active ingredient has insufficient driving force after penetrating the epidermal layer and is difficult to penetrate into the dermal layer.
[0105] Comparative Example 3 contains only menthol carbonate, and its active ingredient has a lower retention rate in the stratum corneum than Comparative Example 2. However, its penetration rate in the dermis is comparable to that of Comparative Example 2, both of which are lower than that of Example 1. This indicates that although monoterpene carbonate can provide a certain driving force and chemical penetration-enhancing effect, its overall penetration efficiency is still not as good as the dual-mode synergistic system due to the lack of an initial driving force for rapid initiation.
[0106] The distribution of the active ingredient in the dermis of Comparative Example 4 was lower than that in Example 1, indicating that the additional function of the terpene group in monoterpene carbonates is to disturb the orderly arrangement of lipids in the stratum corneum and open the permeation channels, giving it a significant advantage over diethyl carbonate. Diethyl carbonate only has conventional permeation-enhancing activity, while the terpene group of monoterpene carbonates can actively play a permeation-enhancing role during the release process.
[0107] The amount of dermal layer retention and the percentage of dermal layer penetration in Comparative Example 5 were significantly lower than those in Example 1. This indicates that adding isosorbide dimethyl ether in advance during the emulsification stage cannot achieve the rapid start-up and long-lasting synergistic effect achieved by adding isosorbide dimethyl ether later in Example 1.
[0108] The above results indicate that the dual-mode driver of isosorbide dimethyl ether and monoterpene carbonate, through the synergistic effect of a triple mechanism of short-acting rapid initiation, long-acting diffusion and sustained maintenance, and active penetration promotion by terpene groups, achieves the gradual advancement and deep accumulation of active ingredients from the stratum corneum to the dermis, truly achieving the technical effect of highly efficient deep penetration.
[0109] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a highly efficient deep-penetrating nanoemulsion, characterized in that, Includes the following steps: S1. Dissolve the additive in deionized water, heat to 40~50℃, and stir until completely dissolved to obtain the aqueous phase; S2. Mix monoterpene carbonate, oil phase matrix, composite emulsifier and active ingredient, heat to 40~50℃, stir until completely dissolved, to obtain oily premix; S3. Under stirring conditions of 40~50℃ and 300~500rpm, the oily premix is slowly injected into the aqueous phase at an injection rate of 1~5mL / min. The non-equilibrium distribution of the composite emulsifier at the oil-water interface generates an interfacial tension gradient, which drives the oil phase to spontaneously break down into nano-sized droplets, thus obtaining a spontaneously emulsified emulsion. S4. Cool the spontaneously emulsified emulsion to room temperature, add isosorbide dimethyl ether under sealed conditions, stir at 200-300 rpm for 5-10 min, and homogenize at room temperature and 300-500 bar pressure for 1-2 cycles to obtain a highly efficient deep-penetrating nanoemulsion. The highly efficient deep-penetrating nanoemulsion, by mass percentage, comprises the following components: 1-3% of additives, 2-6% of isosorbide dimethyl ether and monoterpene carbonate, 6-12% of oil phase matrix, 2-5% of composite emulsifier, 2-4% of active ingredients, and the balance being deionized water. The mass ratio of isosorbide dimethyl ether to monoterpene carbonate is 1:1~2; The preparation method of the monoterpene carbonate is as follows: terpene alcohol is mixed with diethyl carbonate, an alkaline catalyst is added, and the mixture is stirred at 80-100℃ for 4-8 hours. During the reaction, the byproduct ethanol is continuously removed by distillation. After the reaction is completed, the mixture is cooled to room temperature and purified by vacuum distillation and column chromatography to obtain the monoterpene carbonate. The terpene alcohol is menthol or thymol; the alkaline catalyst is sodium ethoxide or potassium carbonate. The adjuvant is prepared by compounding glycerol and sodium hyaluronate; the oil phase matrix is caprylic triglyceride or caprylic triglyceride; the composite emulsifier is prepared by compounding polysorbate 80 and sucrose stearate; the active ingredient is any one of vitamin C ethyl ether, palmitoyl pentapeptide-4, and retinol. The molar ratio of the terpene alcohol to diethyl carbonate is 1:1 to 3; the amount of the alkaline catalyst is 0.5 to 3% of the total mass of the terpene alcohol and diethyl carbonate; the mass ratio of the glycerol to sodium hyaluronate is 3 to 4:1; and the mass ratio of the polysorbate 80 to sucrose stearate is 3 to 5:
1.
2. A highly efficient deep-penetrating nanoemulsion, characterized in that, It is prepared by the preparation method described in claim 1.
Citation Information
Patent Citations
VC-IP nano-liposome with enhanced transdermal absorption effect as well as preparation method and application of VC-IP nano-liposome
CN118806634A
Water-soluble transparent ceramide composition as well as preparation method and application method thereof
CN120420236A
